2012
DOI: 10.1111/hex.12008
|View full text |Cite
|
Sign up to set email alerts
|

A patient perspective of pharmacist prescribing: ‘crossing the specialisms‐crossing the illnesses’

Abstract: Background The drive for non-medical prescribing has progressed quickly since the late 1990s and involves a range of healthcare professionals including pharmacists. As part of a commissioned research project, this qualitative element of a larger case study focused on the views of patients of pharmacist prescribers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 18 publications
(27 reference statements)
3
59
0
6
Order By: Relevance
“…[29,30] The themes related to the pharmacist did not change over the three phases of this study. This acceptance of community pharmacists is consistent with other studies where pharmacists have been involved in chronic disease management as well as independent prescribing.…”
Section: Discussionmentioning
confidence: 82%
“…[29,30] The themes related to the pharmacist did not change over the three phases of this study. This acceptance of community pharmacists is consistent with other studies where pharmacists have been involved in chronic disease management as well as independent prescribing.…”
Section: Discussionmentioning
confidence: 82%
“…The majority of those patients who had consulted with a pharmacist prescriber were highly satisfied with the consultation overall, particularly the pharmacist's competence and capability, considering their prescribing to be as effective and safe as their physician. They also gave positive feedback relating to the pharmacist's personality, knowledge and communication skills as well as the consistency, accessibility, length and outcome of the care received .…”
Section: Resultsmentioning
confidence: 99%
“…Whilst not widely implemented in IC, pharmacist prescribing has become an increasingly commonplace practice in both primary and secondary care settings [18, 19]. Notably, it has been shown that patients generally regard pharmacist prescribing as an acceptable alternative to medical prescribing [20, 21]. This study suggests that CPs are keen to expand their professional boundaries, however, it remains the case that the majority of those who have acquired prescribing qualifications are currently not using them, perhaps due to a lack of opportunities or lack of access to clinical information in the community pharmacy setting necessary to facilitate a prescribing role.…”
Section: Discussionmentioning
confidence: 99%
“…This finding reiterates that reported in the previous qualitative study [3], where it was described how CPs were not routinely informed when patients were admitted into hospital or IC. This issue is not unique to NI [21]. Irrespective of the setting, only a minority of CPs reported that they were informed of changes to patients’ medication regimens ‘ all of the time ’ at discharge.…”
Section: Discussionmentioning
confidence: 99%